Pengaruh Stability Ball Exercise dan Lumbopelvic Exercise terhadap Aktifitas Fungsional pada Ibu Hamil dengan Kondisi Nyeri Punggung Bawah Postural - Intan Yusita; Antri Ariani; Cici Valiani; Sinta Putri Oktaviani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
There are late stage pregnancy complaints that are felt such as low back pain, pelvic pain, pubic symphysis dysfunction, carpal tunnel syndrome, and stress incontinence.(1) Nyeri punggung have anegative impact on daily activities such as when walking, lifting things, climbing stairs, lying on your back, exercising, doing household chores, even at rest and tidur.(3) Stability Ball Exercise is a lumbar dynamic stability exercise to reduce low back pain, increase muscle strength, endurance, balance, and flexibility reflexes.(4) Lumbopelvic exercise is a stretching and strengthening exercise that focuses on strengthening the back and abdominal muscles that function as stabilizers in the lumbopelvic so as to increase the activity ability of functiononal.(5)The purpose of this study was to identify the Effect of Stability Exercise and Lumbopelvic Exercise on Functional Activities in Pregnant Women With Postural Lower Back Pain Conditions. The research method used is quasi-experimental with a time-series experimental design research approach. This study was conducted using the oswestry disability index (ODI) instrument. The results of the study with the anova test obtained differences in the average ODI score before and after the Stability Ball Exercise and lumbopelvic exercise with a sig value of 0.000<0.05, it can be concluded that the variant group has an average ODI score which has a significant effect on increasing functional activity. Can be used as an alternative to gymnastics for pregnant women in services in independent midwifery practice and can improve the quality of comprehensive midwife-based care services.